(untitled) (Journal of the College of Basic Education, 2022)
Cognitive styles are among the basic and important methods in cognitive psychology because they relate to the feelings of individuals and their behavior in the face of various life situations. The cognitive style (impulsive - reflective) is one of these methods that depend on it mainly to distinguish between individuals for their speed of response to life situations and their accuracy. The current research aims to identify1- Cognitive style (reflective - impulsive) among middle school students2- Personality traits of middle school students3- Statistically significant differences in the cognitive style (impulsive - reflective) among middle school students4- The correlation between cognitive style and personality traits, and for the purpose of achieving the research objectives, the researcher adopted a scale